2011
DOI: 10.1016/j.neuron.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Translating Stem Cell Studies to the Clinic for CNS Repair: Current State of the Art and the Need for a Rosetta Stone

Abstract: Since their discovery twenty years ago and prospective isolation a decade later, neural stem cells (NSCs), their progenitors, and differentiated cell derivatives along with other stem-cell based strategies have advanced steadily toward clinical trials, spurred by the immense need to find reparative therapeutics for central nervous system (CNS) diseases and injury. Current phase I/II trials using stem cells in the CNS are the vanguard for the widely anticipated next generation of regenerative therapies and as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
140
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 63 publications
1
140
0
5
Order By: Relevance
“…Although engrafted NSPCs could facilitate functional recovery after SCI through multiple mechanisms 4,5,8 , our results revealed that neuroprotective effect is most significant for acute phase of SCI. Furthermore, we directly confirmed the neurohumoral secretion of engrafted NSPCs and demonstrated their secretory activities to be mostly enhanced after transplantation.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Although engrafted NSPCs could facilitate functional recovery after SCI through multiple mechanisms 4,5,8 , our results revealed that neuroprotective effect is most significant for acute phase of SCI. Furthermore, we directly confirmed the neurohumoral secretion of engrafted NSPCs and demonstrated their secretory activities to be mostly enhanced after transplantation.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, using BLI, we demonstrated the presence of an appropriate range in the number of transplanting cells for SCI. In clinical trials, the transplantation protocols are completely different and, in particular, the number of transplanted cells varies considerably, which is also true in animal studies 5,7,8 . This hampers the establishment of an optimal treatment for SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aboody et al [10] provides an excellent review of ongoing clinical trials using stem cell-mediated approaches in the CNS (see Table 3). Although it is impossible to discuss each disease model in detail, certain generalizations are possible.…”
Section: Possible Modes Of Action Of Engrafted Cellsmentioning
confidence: 99%